AI INTEGRATION IN ENGLISH LANGUAGE TEACHING: INSIGHTS INTO ESP TEACHERS’ VIEWS AND READINESS - Sari, Latifa Ika; Sari, Ria Hermina (English Review: Journal of English Education, 2025)
This study investigates ESP teachers’ perspectives on the integration of AI tools in language teaching, focusing on the benefits, negative sides, usage, readiness, and barriers they face. A qualitative approach was employed, utilizing an open-ended questionnaire distributed to 30 teachers in higher vocational institutions. The thematic analysis of their responses reveals several findings. Teachers recognize AI's potential to support personalized learning, enhance skill development, and assist in lesson planning. However, concerns about over-reliance on AI and the lack of human interaction were also highlighted. Additionally, the study identifies barriers such as inadequate training, infrastructure limitations, and ethical concerns. Teachers emphasized the need for professional development programs, including technical training, AI integration in pedagogy, and ethical guidance. Institutional support in providing access to AI resources and managing workloads is also critical. The study suggests a balanced integration of traditional methods and AI-driven approaches.